The danger of "fake news": how using social media for information dissemination can inhibit the ethical decision making process. Issue 4 (19th May 2022) - Chauhan, Rahul S.; Connelly, Shane; Howe, David C.; Soderberg, Andrew T.; Crisostomo, Marisa
ABSTRACT: Social media is becoming increasingly embedded in people's daily lives. These virtual spaces are now regularly used as a tool for information dissemination. Drawing on the moral intensity literature combined with uses and gratifications theory, this research explores how using social media to consume information can affect the ethical decision-making process. This study compares the influence of two online media dissemination formats – an online news article and social media discussion thread – on individuals' ethical perceptions and decisions. Results indicate that social media usage has an effect on perceptions of social consensus, problem recognition, and ethical sensemaking. Overall, Social media is shown to inhibit ethical decision-making when used as an information dissemination tool.